2018
DOI: 10.1038/s41436-018-0005-9
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of pathogenic variations in a panel of 34 genes and cancer risk estimation from 5131 HBOC families

Abstract: Our results validate the integration of PALB2, RAD51C, and RAD51D in the diagnosis of HBOC and suggest that the other genes are involved in an oligogenic determinism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
46
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 41 publications
(51 reference statements)
9
46
4
Order By: Relevance
“…While the highest prevalence of BRCA1/2 mutation carriers was in patients diagnosed with double primary OC and BC, mutations in RAD51C/RAD51D/BRIP1 prevailed in patients diagnosed with OC only ( Figure 2B); nevertheless, their distribution among histological subtypes was similar to that in BRCA1/2 mutation carriers ( Figure 2E). In contrast to Castera et al who found mutations in RAD51C/RAD51D/BRIP1 dominantly in French OC patients with a positive family OC history [32], we identified mutations in these genes in 1/116 (0.9%) and 22/587 (3.7%) carriers in HOC patients and in patients with a negative family cancer history, respectively. Further, we have noticed a surprisingly high frequency of OC-predisposing mutations in older patients.…”
Section: Discussioncontrasting
confidence: 99%
“…While the highest prevalence of BRCA1/2 mutation carriers was in patients diagnosed with double primary OC and BC, mutations in RAD51C/RAD51D/BRIP1 prevailed in patients diagnosed with OC only ( Figure 2B); nevertheless, their distribution among histological subtypes was similar to that in BRCA1/2 mutation carriers ( Figure 2E). In contrast to Castera et al who found mutations in RAD51C/RAD51D/BRIP1 dominantly in French OC patients with a positive family OC history [32], we identified mutations in these genes in 1/116 (0.9%) and 22/587 (3.7%) carriers in HOC patients and in patients with a negative family cancer history, respectively. Further, we have noticed a surprisingly high frequency of OC-predisposing mutations in older patients.…”
Section: Discussioncontrasting
confidence: 99%
“…PALB2 is a crucial regulator in maintaining genome integrity, while its dysfunction leads to breast cancer predisposition. The clinical relevance of PALB2 has been partially described, and PALB2 is reported to be a highrisk breast cancer susceptibility gene comparable to BRCA2 (16). With the identification of deleterious PALB2 recurrent mutations and PARPi, individualized risk assessment and precision medicine for PALB2 mutation-associated breast cancer become possible.…”
Section: Discussionmentioning
confidence: 99%
“…However, the high-penetrance BRCA1 and BRCA2 are responsible for only ∼20% of the familial aggregation of breast cancer (12,13), and syndromic breast cancer susceptibility genes such as TP53, PTEN, and CDH1 are estimated to explain just 5% of familial breast cancers (14). Large-scale analyses of multigene panel testing recently confirmed PALB2 as a high-risk breast cancer susceptibility gene (15), and the odds ratio (OR) of PALB2 mutations for breast cancer was comparable to that of BRCA2 mutations (16). Hence, a comprehensive understanding of the biological functions of PALB2 is vital for breast cancer management and precision medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies of cases selected for a family history of breast or ovarian cancer found that 24–76% had deleterious variants in BRCA1 and 1–17% had deleterious variants in BRCA2 [ 17 ]. Recent studies using clinical testing laboratory data have reported the prevalence of BRCA1/2 pathogenic variants in 5020 and 7489 cases from the USA [ 26 , 27 ], 4409 cases from France [ 28 ], and 3230 cases from a meta-analysis of 48 multi-gene panel testing-based studies [ 29 ]. In these studies, the frequency of germline pathogenic variants in BRCA1 in ovarian cancer cases were 5.1%, 3.6%, 3.7%, and 8.6%, respectively, and 3.9%, 3.3%, 4.0%, and 4.5% in BRCA2 [ 26 , 27 , 28 , 29 ].…”
Section: Protein Truncating Variants In Confirmed Susceptibility Gmentioning
confidence: 99%